2020
DOI: 10.1016/j.adolescence.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Non‐suicidal self‐injury in adolescence: Longitudinal evidence of recursive associations with adolescent depression and parental rejection

Abstract: Introduction: Non-suicidal self-injury (NSSI) has been acknowledged as a major public health concern among adolescents. However, the complex association between parental rejection and NSSI is not entirely understood and the existing literature does not address the underlying mechanism of adolescent depressive symptoms in explaining the process. Methods: Three waves of data (called T1, T2 and T3) were collected 6 months apart, between November 2018 and 2019, in a sample of 1987 Chinese adolescents (56.1% males;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…This result is congruent with the experiential avoidance model [ 43 ] which postulates that conflict with parents elicits an emotional response (i.e., depressive symptoms) in order to escape to loathsome emotional experiences, which in turn prompted their NSSI. This result is consistent with findings from previous studies that a negative family environment is an important factor for adolescent NSSI via the mediating effect of depressive symptoms [ 14 , 16 , 44 ]. Apart from the overall mediation results, each and every individual link in the mediation model of depressive symptoms is noteworthy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is congruent with the experiential avoidance model [ 43 ] which postulates that conflict with parents elicits an emotional response (i.e., depressive symptoms) in order to escape to loathsome emotional experiences, which in turn prompted their NSSI. This result is consistent with findings from previous studies that a negative family environment is an important factor for adolescent NSSI via the mediating effect of depressive symptoms [ 14 , 16 , 44 ]. Apart from the overall mediation results, each and every individual link in the mediation model of depressive symptoms is noteworthy.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Valencia-Agudo et al retrieved 39 studies on NSSI indicated that depressive symptoms is observed to prospectively predict future NSSI [ 13 ]. Furthermore, preliminary research suggested that depressive symptoms played an important mediating role between family risk factors (e.g., parental rejection, harsh parenting) and adolescent NSSI [ 14 , 15 , 16 ]. A longitudinal research by Zhu et al, with a sample of 1987 Chinese adolescents, found that parental rejection predicted adolescents NSSI six months later through depressive symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our models do not provide evidence of causality, and prior research found that the effects between self‐injury and, for example, depressive symptoms can be reciprocal (Zhu, Chen, & Su, 2020 ). Nevertheless, our results support the conclusion that effects operated from stressors to harm, given that all models, including the mediation models, controlled for prepandemic individual differences in self‐injury or violence, respectively, and emotions.…”
Section: Discussionmentioning
confidence: 55%
“…We measured adolescents' depression with a 20-item Chinese version (Zhu, Chen, & Su, 2020) of the Center for Epidemiologic Studies Depression Scale for Children (CES-CD) which has been shown good reliability in previous research in China (William et al, 2010). Adolescents were asked to indicate the frequency of their depressive symptoms during the past week (e.g., "I was bothered by things that usually don't bother me").…”
Section: Depressionmentioning
confidence: 99%